2019
DOI: 10.5101/nbe.v11i1.p11-17
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic and Genotypic Detection of Biofilm Formation Pseudomonas oryzihabitance and Susceptibility to Antibiotics

Abstract: Pseudomonas oryzihabitans is uncommon pathogen, but recently there may be warning of this bacterium to be dangerous, highly virulence, and may cause increase in morbidity and mortality rate, especially if there are multi-drug resistance and biofilm former. Biofilm forming bacteria display resistance to antibiotics, reaching to 1000 time higher than planktonic bacteria. The aim of the current study was to detect Pseudomonas oryzihabitans as biofilm producer and determine the susceptibility to the tested antibio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 31 publications
1
6
0
Order By: Relevance
“…Ksontini and co author, pointed that dairy biofilm formation depends on the types of surface material and bacterial community that investigated the biofilm formation based on thermodynamic approach (17). Antibiotic susceptibility profile by Vitek AST to K. pneumonia and E. coli (Table 1) revealed that both biofilm forming bacteria were resistant to most antibiotics used in this test which was confirmed by the previous studies (18,19). The MIC breakpoints according to M100 (20)…”
Section: Figure 2 Congo Red Agar Indicating the Biofilm Formation Bacteriasupporting
confidence: 66%
See 1 more Smart Citation
“…Ksontini and co author, pointed that dairy biofilm formation depends on the types of surface material and bacterial community that investigated the biofilm formation based on thermodynamic approach (17). Antibiotic susceptibility profile by Vitek AST to K. pneumonia and E. coli (Table 1) revealed that both biofilm forming bacteria were resistant to most antibiotics used in this test which was confirmed by the previous studies (18,19). The MIC breakpoints according to M100 (20)…”
Section: Figure 2 Congo Red Agar Indicating the Biofilm Formation Bacteriasupporting
confidence: 66%
“…The biofilm-forming bacteria displayed antibiotics resistant patterns. Many studies approved that biofilm bacteria were multi-drug resistance bacteria (18,19,21,22). The reasons behind their resistance were antibiotics penetration difficulty(23), extracellular matrix act at shield and chelating agent (24) and low bacterial metabolic state (25).…”
Section: Figure 2 Congo Red Agar Indicating the Biofilm Formation Bacteriamentioning
confidence: 99%
“…From the previous study [26], it was found that imipenem antibiotic was the most effective antibiotic on biofilm P. oryzihabitans. To study the synergism effect between AgNPs in both types and imipenem, the combination with each other was carried out.…”
Section: Combination Both Types Of Agnps With Imipenemmentioning
confidence: 95%
“…Biofilm-forming bacterial isolates (P. oryzihabitans) were isolated and identified according to previous study [26].…”
Section: Experimental Bacterial Isolatesmentioning
confidence: 99%
“…Pseudomonas oryzihabitans is a gram negative yellow pigmented, oxidase negative, rod shaped bacteria (Hasson, 2019). It is an opportunistic pathogen of humans and warm-blooded animals and known to cause septicemia, peritonitis, endophthalmitis, skin and soft tissue infections, and bacteremia (Freney et al, 1988;Panagopoulos et al, 2016;Tena & Fernández, 2015;Woo et al, 2014).…”
Section: Bacillus (Bmentioning
confidence: 99%